Tumor odontogênico queratocístico - Igreja, Bruna Babler [UNESP] (2011)
The keratocystic odontogenic tumor (KCOT), formerly known as keratocystic odontogenic parakeratinized, was classified as benign tumour by the WHO in 2005. The tumour has a large proliferative potential and its recurrence is frequent, essential factor for its classification as a neoplasm. The fibrous capsule is thin, friable, occasionally showing micro cysts and no inflammatory infiltrate. This paper aims to describe information and to present a case of a KCOT in the anterior jaw region of a male patient, aged 63, whose main complaint was a sensation of anesthesia in the vestibular region of the gum, between 33 and 34. The conduct was held aspiration and excisional biopsy. After 18 months of control, with radiographic findings showed poor bone formation and possible recurrence. New surgery was performed with an auxiliary method of cryotherapy. Patient has recovered well and continues in proservation